Job Enrichment and Its Influence in Organizational Cynicism among Workers in Iraqi Youth and Sport Forums - Ghadhban, Saba Qays; Abbas, Rawaa Abdulameer; Sabit, Siham Hammood (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to (1) identify the level of job enrichment and organizational cynicism among workers in some youth and sport forums, and (2) identify the influence the job enrichment in the organizational cynicism from their perspective. A descriptive survey was used to guide this study. The study included 478 workers who were randomly selected from the youth and sport forums in Baghdad City in 2019. The Job Enrichment Scale and the Organizational Cynicism Scale were used. Data were analyzed using the statistical package for social science, version 26. The study results revealed that the level of job enrichment and organizational cynicism among workers were unsatisfactory. This calls for paying more attention to these phenomena and improve their levels as they have positive effect for these forums in achieving their objectives and missions for the community. The job enrichment inversely correlates to the organizational cynicism in that the higher the job enrichment, the lower the organizational cynicism. Furthermore, it is necessary to find an international mechanism for understanding that helps in developing and improving the workers’ abilities from one side, and the administrative work in the youth and sport forums in Iraq from the other side, and benefit from the expertise of the countries advanced in the sport field for the sake of serving the movement of the Olympic sport and discriminating the peace and lenience among communities.